Melatih Keterampilan Berpikir Kreatif Siswa Kelas X Melalui Model Project-Based Learning dengan Pendekatan STEM - Ulfa Alfiana; Gunawan Gunawan; Wahyudi Wahyudi; Zulkipli Hamdani (Indonesian Journal of Education and Community Services, 2026)
This activity was conducted to introduce and implement a STEM-integrated Project-Based Learning (PjBL) model to enhance the creative thinking skills of tenth-grade students. The activity took place at SMA Negeri 1 Lingsar. The implementation was motivated by the school’s need to strengthen 21st-century skills, particularly creativity, collaboration, communication, and problem-solving, through interactive and challenging learning experiences that utilize diverse learning resources. The focus of the activity was directed toward the integration of Science, Technology, Engineering, and Mathematics (STEM) through various modes of presentation, such as text, images, audio, and video, designed to support systematic and creative problem-solving processes. The stages of the activity included the introduction of the STEM-integrated PjBL concept, project planning, implementation of projects based on contextual problems, and the presentation and reflection of students’ work. The results indicated that both teachers and students responded positively to this approach. STEM-integrated project-based learning encouraged students to become more active, creative, and   collaborative, while also helping them develop a deeper understanding of physics concepts   through meaningful learning experiences. Overall, this activity recommends STEM-integrated PjBL as an effective alternative strategy for physics instruction to foster students’ creative thinking skills at the senior high school level.